2006
DOI: 10.1128/ec.00156-06
|View full text |Cite
|
Sign up to set email alerts
|

Galactose Starvation in a Bloodstream Form Trypanosoma brucei UDP-Glucose 4′-Epimerase Conditional Null Mutant

Abstract: Galactose metabolism is essential for the survival of Trypanosoma brucei, the etiological agent of African sleeping sickness. T. brucei hexose transporters are unable to transport galactose, which is instead obtained through the epimerization of UDP-glucose to UDP-galactose catalyzed by UDP-glucose 4-epimerase (galE). Here, we have characterized the phenotype of a bloodstream form T. brucei galE conditional null mutant under nonpermissive conditions that induced galactose starvation. Cellular levels of UDP-gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 23 publications
(34 reference statements)
2
59
0
Order By: Relevance
“…For these reasons, we believe that the MRM method is a good tool for detecting and quantifying low-abundance sugar nucleotides, such as UDP-Galf, UDP-Xyl, GDP-Ara, and GDP-Fuc, from relatively small culture volumes (10 to 100 ml). The method has already proved useful in characterizing sugar nucleotide levels for two UDP-Gal 4Ј-epimerase-deficient cell lines (62,120) and will be applied to other trypanosome mutants to monitor the effects on sugar nucleotide levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, we believe that the MRM method is a good tool for detecting and quantifying low-abundance sugar nucleotides, such as UDP-Galf, UDP-Xyl, GDP-Ara, and GDP-Fuc, from relatively small culture volumes (10 to 100 ml). The method has already proved useful in characterizing sugar nucleotide levels for two UDP-Gal 4Ј-epimerase-deficient cell lines (62,120) and will be applied to other trypanosome mutants to monitor the effects on sugar nucleotide levels.…”
Section: Discussionmentioning
confidence: 99%
“…The only route to UDP-Galp in bloodstream and procyclic-form T. brucei and epimastigote form T. cruzi is via the epimerization of UDPGlc, because their hexose transporters are unable to transport Gal (9,112). The UDP-Glc 4Ј-epimerase (GalE) responsible for this interconversion is essential in both life cycle stages of T. brucei (96,97,120) and appears to be essential for T. cruzi epimastigotes (62), suggesting that this enzyme may be a good therapeutic target against African trypanosomiasis and possibly Chagas' disease.…”
Section: Cruzi) Gdp-man Is Also the Precursor Of Gdp-fuc (See Below)mentioning
confidence: 99%
“…This may explain why GalNAc has yet to be found in any glycoconjugates of this parasite. (b) All the enzymes identified in the biosynthesis of the above five nucleotide sugars were localized to the glycosomes (44,46,59,(61)(62)(63), which are microbodies evolutionarily related to peroxisomes in higher eukaryotes and their function is essential in carbohydrate metabolism in T. brucei. However, in its mammalian hosts, most nucleotide sugars are synthesized in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that enzymes involved in nucleotide sugar biosynthesis in T. brucei such as UDP-Gal (59,61,78), GDP-Fuc (62), GlcNAc (63), and GDP-Man are essential for cell growth, but none of them were shown to cause pathogenicity changes in BSF T. brucei. We speculate that the function of the totality of TbNSTs is essential for cell growth and that inhibition of a specific or multiple tbnst involved in glycosylation of essential proteins for virulence will change the parasites' infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is essential in unicellular parasites from the genus Trypanosoma since they are unable to take up galactose from the environment and rely on "reversing" some of the Leloir pathway reactions in order to generate galactose for glycoprotein synthesis [207][208][209][210][211]. Thus, inhibition of GALE in these species has potential for the development of novel therapeutics [212][213][214][215].…”
Section: Other Metabolic Pathwaysmentioning
confidence: 99%